A select library of the Nicene and Post-Nicene Fathers of the Christian church - Augustin, Saint; Augustine, Saint; Schaff, Philip 1819-1893 (Edinburgh, Scotland T and T Clark, 1889)
Contents: v. IV : St Augustin / The writings against the Manichaeans ; The writings against the Donatists. Includes indexes.
Keywords: Fathers of the church -- Primitive and early church -- ca 30-600.; Augustin, Saint; Augustine, Saint